The treatment of temporality in medieval and modern history classes in higher education (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
Historical time is a fundamental epistemological category to explain historical processes and it is generally assumed that students understand it by simply reading and studying historiographical texts. However, the difficulties presented by students in a History Teaching Training programme and a Bachelor's Degree in History of the Faculty of Humanities and Sciences suggest that a more systematic approach to temporality in the history class is required. Given our experience in teaching the classes of Medieval Societies and Formation of the Modern World I, in this work we intend to describe and analyze activities, resources and materials used in teaching certain historical events and processes of medieval societies and early modernity, starting with basic notions about time and its relations with history. The main sources of this work are the different temporal graphic representations that have been prepared to teach different topics in the subjects mentioned above as well as their methodological development and students’ reception of such activities and materials.
Keywords: temporal categories; historical time representations; Medieval and Modern History; higher education